The Clinical Significance of Small Vessel Vasculitis on Temporal Artery Biopsies. Issue 2 (15th June 2022) - Quigley, Julian; Sammel, Anthony Michael; Laurent, Rodger; Brewer, Janice; Hsiao, Edward; Schembri, Geoffrey; Fraser, Clare L.
Abstract : Background: Giant cell arteritis (GCA) is the most common type of systemic vasculitis in the elderly. Untreated, it can lead to irreversible blindness. Its diagnosis relies on a temporal artery biopsy (TAB). However, a proportion of patients have small vessel vasculitis (SVV) on biopsy; the prognosis of which remains unclear. The aim of this study is to compare the clinical presentation and long-term outcomes of those with SVV with negative and positive biopsies to determine whether long-term corticosteroid therapy can be avoided in these patients. Methods: Post hoc analysis of patients with suspected GCA who underwent TAB and fluorodeoxyglucose positron emission tomography/computed tomography (PET/CT) scan as part of a prospective GCA and PET cohort. Patients were divided in to 3 groups based on TAB result: positive (inflammation in the main artery wall), negative (no inflammation), and SVV (isolated vasa vasorum or periadventitial SVV). Clinical, serological, and PET/CT data of patients with SVV were compared with those with positive and those with negative biopsies. Results: For the 58 eligible patients recruited between May 2016 and December 2017, 11 had SVV, 12 had positive, and 35 had negative biopsies. Patients with SVV had similar clinical, serological, and PET/CT findings to those with negative biopsies. Compared with those with positive biopsies, patients with SVV had lower erythrocyte sedimentation rate (25 vs 78 mm/hour; P = 0.02), platelet count (296 vs 385 ×10 9 /L; P = 0.03), and a lower median total vascular score on PET/CT scan (1.0 vs 13.5; P = 0.01). Median prednisone dose was lower (4.8 vs 11.7 mg; P = 0.015) and fewer were on steroid-sparing agents (20% vs 67%; P = 0.043) at 6 months. The percentage of patients with a clinical diagnosis of GCA was similar between those with SVV (3/11, 27.3%) and those with negative biopsies (5/35, 14.3%; P = 0.374). Conclusions: Patients with SVV on TAB had similar clinical features, PET/CT findings, and 6-month outcomes to those with negative biopsies. Small vessel vasculitis can be treated as equivalent to a negative biopsy when being considered for diagnosis and treatment of GCA.